Pengaruh Himbauan Gubernur Bali Tentang Penggunaan Baju Endek Terhadap Peningkatan Produksi, Penjualan Dan Trend Fashion Endek Bali Pada Prabu Kreasi Tabanan - Sudiartini, Ni Wayan Ari; Indiani, Ni Luh; Sriwidani, Ni Luh Dewi (Jurnal MBE Manajemen Bisnis, Equilibrium, 2022)
In accordance with the results of the research and discussion above regarding the problem of the relationship between the independent and dependent variables, it can be explained as follows: obtained from a significant F value of 0.000 and a significance value of 0.000 <0.05 indicating that Ho is rejected and H1 is accepted. The influence of the Bali Governor's appeal variable on the production variable obtained a significance value of 0.000 less than 0.05 (0.000 <0.05) with a regression coefficient value of 0.511 which is positive, in other words the Bali Governor's appeal has a positive and partially significant effect on Bali endek production. to Prabhu Kreasi Tabanan. The influence of the Bali Governor's appeal variable on the sales variable obtained a significance value of 0.004 less than 0.05 (0.004 <0.05) with a regression coefficient value of 0.849 which is positive, in other words the Bali Governor's appeal has a positive and partially significant effect on Bali endek sales. to Prabhu Kreasi Tabanan. The influence of the Governor of Bali's appeal variable on the fashion trend variable obtained a significance value of 0.012 less than 0.05 (0.012 <0.05) with a regression coefficient of 0.682 which is positive, in other words the Governor of Bali's appeal has a positive and partially significant effect on fashion trends endek of Bali on Prabhu Kreasi Tabanan.